2020
DOI: 10.1111/jph.12951
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sources of resistance to common bacterial blight in common bean in Ethiopia

Abstract: Common bacterial blight (CBB) caused by Xanthomonas axonopodis pv. phaseoli and X. axonopodis pv. phaseoli var. fuscans is one of the major biotic constraints limiting common bean (Phaseolus vulgaris L.) production and productivity in Ethiopia. The objective of this study was to identify new sources of CBB resistance from a diverse panel of genotypes to develop CBB‐resistant common bean varieties. One hundred and ten diverse accessions were evaluated for CBB resistance at three hotspot sites (Melkassa, Arsi Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Hence, it could be evidence to get sources of disease resistance from elite lines, landraces and released varieties, probably also from gene pools could be used in the common bean breeding system. In this regard, studies by Tumsa et al (2020) tested 110 bean genotypes and found that 32 of the genotypes had superior CBB resistance reaction and agronomic performances which confirm for the present finding. Similarly, Adila et al (2021) reported that common bean genotypes performed variably to CBB infections, grain yield and yield components under field conditions.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Hence, it could be evidence to get sources of disease resistance from elite lines, landraces and released varieties, probably also from gene pools could be used in the common bean breeding system. In this regard, studies by Tumsa et al (2020) tested 110 bean genotypes and found that 32 of the genotypes had superior CBB resistance reaction and agronomic performances which confirm for the present finding. Similarly, Adila et al (2021) reported that common bean genotypes performed variably to CBB infections, grain yield and yield components under field conditions.…”
Section: Discussionsupporting
confidence: 88%
“…Variable reactions among the genotypes showed the possibility of obtaining genes for resistance and confirmed the presence of genes for resistance having varying genetic potentials to adjust under different environments ( Rezene and Mekonin, 2019 ; Tumsa et al., 2020 ; Adila et al., 2021 ). Beebe et al.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations